CAMBIOS MORFOLÓGICOS DEL COMPLEJO DENTO-ALVEOLAR EN ESTADOS CARENCIALES DE VITAMINA A: Estudio Experimental - Galvez, Luis (1998)
We used 20 rats, white males, breed Holstman with 21 days age. After 35 days of birth, the specimens were grouped in 2 group of l0 each, aleatory conformed; one control and other test. Immediately both group were placed within very strict dietetic regime, this was made according to Mendez, during the rest of time of research process. In addition, the control group received a weekly dosis of 100 U. I. of retinol with a faringeal catheter to complete the dietetic normal balance. After the seven and eight week of experimental phase, the animals were sacrificed by decapitation and the mandibular regions were dissected and sumerged in formol 10% for more of 72 hours. After the normal Procedure of descalcification in nitric acid 10% the tissues were seccionated in mandibulars hemi arch left and right, those blockeds were subdivided in 2 additional subblockes, one molar and other incisive. Later on botth were embedding in paraplast, sectionated a 5 of thickness and colored with hematoxilyn and eosin. The histological analysis of the tissues within the odontogenic base of the incisors of rat with avitaminosis A shown acid resistant enamel apposition which goes from 0 to 3 of thickness (Fig. 3), with cy cylindrical ameloblasts inhibited funcionally and in some with lost of their conextion plasmatic union complex side. Further of the odontogenic base, the aineloblastic epitelium was manteined morphological normal; howerwe, in some cases the spaces interameloblastic reduced same as the proximal existant in the enamel maturetion phase. Besides, it shows differentiation of bucal adontoblasts with reduced production of dentine matrix and absence of lingual odontoblast (Fig. 3), the dental pulp next to the specialized cells is mesenquimatic and vascularized (Fig. 3). The transverse and longitudinal histological cuts of the crown of molars with avitaminosis A, shown a pulpodentinary complex with lack of production of predentine, and in some cases almost unexistant. It was observed bodies of odontoblasts in relation with the internal front of dentinary mineralization. The periodontal complex shown a relative enlargement of the alveolar crest without sign of renzodelation (Fig. 4); however it does appear morfological changes apparent. The morfological changes of the complex dentoalveolar existent in cases of avitaminosis A (Hypothesis of this research), tested with Chi Square at a level of confidence of 99% is highly meaningful, except of the periodontal ligament witch is presuntively and the radicular cement is not significant.